Computational models of ventricular mechanics and adaptation in response to right-ventricular pressure overload - Odeigah, Oscar O.; Valdez-Jasso, Daniela; Wall, Samuel T.; Sundnes, Joakim (Frontiers in Physiology, 2022)
Pulmonary arterial hypertension (PAH) is associated with substantial remodeling of the right ventricle (RV), which may at first be compensatory but at a later stage becomes detrimental to RV function and patient survival. Unlike the left ventricle (LV), the RV remains understudied, and with its thin-walled crescent shape, it is often modeled simply as an appendage of the LV. Furthermore, as the RV remodeling caused by PAH will often leave the LV and systemic circulation largely unaffected, this makes the condition harder to detect and diagnose. Several treatment strategies such as atrial septostomy, RV-assist devices or RV resynchronization therapy have been shown to improve RV function and the quality of life in patients with PAH. However, evidence of their long-term efficacy is limited and lung transplantation is still the most effective and curative treatment option. As such, the clinical need for improved diagnosis and treatment of PAH drives a strong need for increased understanding of drivers and mechanisms of RV growth and remodeling, and more generally for targeted research into RV mechanics pathology. Computational models stand out as a valuable supplement to experimental research, offering detailed analysis of the drivers and consequences of growth and remodeling, as well as a virtual test bench for exploring and refining hypotheses of growth mechanisms. In this review we summarize the current efforts towards understanding RV growth and remodeling processes using computational approaches such as reduced-order models, three dimensional finite element models, and growth and remodeling models. In addition to an overview of the relevant literature of RV computational models, we discuss how the models have contributed to increased scientific understanding and to potential clinical treatment of PAH patients.